(untitled) (Reflection and Critique Law Magazine, 2022)
The work to examine, through a doctrinal and legislative study, the feasibility of using the Theory of Fact Mastery in procedural issues subordinate to corruption, as in Criminal Action 470, “mensalão”, judged by the Supreme Federal Court and lawsuit nº 5046512-94.2016.4.04.7000, “Operação Lava-Jato” to the detriment of former President Luiz Inácio Lula da Silva, signed by the Federal Regional Court of the 4th Region. We intend to clarify the conceptual divergences of the aforementioned theory before the Brazilian legal system. Finally, to establish the pertinent idiosyncrasies for the sloppy execution of foreign legal words incompatible with the legislation and concepts already obstinate in Brazil.